STRATEGI USTADZ DALAM MEMBENTUK SIKAP SOPAN SANTUN SANTRI DI PONDOK PESANTREN - Wasilah Puji Lestari; Andi Warisno; Riskun Iqbal; Finy Muslihatuz Zahro’ (UNISAN JURNAL, 2022)
This study aims to determine the politeness of students in the Hidayatul Mubtadiin Islamic Boarding School environment. The type of research in this study used field research (Field Research) and used a qualitative research approach. Data collection methods include: interviews, documentation and observation. The results of the study show that the Ustadz at the Hidayatul Mubtadiin Islamic Boarding School has a strategy in providing guidance to the students in terms of saying good greetings, when meeting with older ones such as teachers, Ustadz , Ustadz ah including the abah kyai and the nyai’s mother must bow. Not only that, students must also dress neatly, politely and also behave well in Islamic boarding schools and in society. And also the factors that encourage Ustadz in forming the polite attitude of students at the Hidayatul Mubtadiin Islamic Boarding School are that many students do not understand the importance of being polite, for example such as violating the rules of the boarding school, being impolite towards the administrators, saying dirty words, or lying to the administrators. Therefore, the Ustadz is obliged to provide direction or guidance so that these students do not commit these violations again and comply with the regulations set at the Hidayatul Mubtadiin Islamic Boarding School.